(untitled) (Analysis in Theory and Applications, 2020)
In this paper we prove two theorems on the degree of approximation of continuous functions by matrix means related to partial sums of a Fourier series in the Hölder metric. These theorems can be taken as counterparts of those previously obtained by T. Singh [3].